Engineering Education: Transformation for Industry 4.0 (SYNERGY 2019 Conference Results Review) - V. V. Kondratyev; M. F. Galikhanov; P. N. Osipov; F. T. Shageeva; A. A. Kaybiyaynen (Высшее образование в России)
The article summarizes the results of the plenary session of the international conference «Engineering education: transformation problems for industry 4.0 SYNERGY-2019», held at the Kazan National Research Technological University from 4 to 5 September 2019. Forum which brought together representatives of universities and industrial enterprises of Russia and abroad, was devoted to the training of engineers of the petrochemical industry. Among its delegates were representatives of international societies for engineering education, five national research universities and nine supporting universities of PC «Gazprom», state authorities and industrial enterprises of Tatarstan. It was possible to observe the work of the plenary session in real time on the Internet in all the supporting universities of Gazprom. The event was organized by the Ministry of Science and Higher Education of the Russian Federation, the International Society for Engineering Pedagogy IGIP, the National Fund of Training of Staff (NFTS), the Association of Engineering Education of Russia (AEER) as well as the Ministry of Industry and Trade of Tatarstan and the Kazan National Research Technological University. The General sponsor was the Public Joint Company «Gazprom». The conference gathered 155 participants from 15 universities of Russia, Kazakhstan and Estonia. Representatives of 11 industrial enterprises spoke, 55 reports made presentations.